GALLIC ACID AND GLUTAMIC ACID CRUDE EXTRACT of SAN-SANGK (Albertisia papuana Becc.) LEAVES by Aspergillus niger FNCC 6018 FERMENTATION at pH and TEMPERATURE VARIETY CONDITION - Ani Nurhayati; Sulvi Purwayanti; Sholahudin . (Jurnal Sains Pertanian Equator, 2019)
One of methods to gallic acid plant productionbytannin fermentation using Aspergillus microbes. The purposeof this research were to obtain gallic acid and glutamic acid from san-sangk (Albertisia papuana Becc.) leaves fermentation using Aspergillus niger FNCC 6018. Research design used factorial block randomized between temperature (25; 30; 45°C) and pH (5; 5.5; 6). The data such as total of tannin (TT) was measuring as a tannic acid while gallic acid was measured from total of phenolic (TF) and glutamic acidwas measured from total of free amino acid (TAAB). Data was analyzed byAnova (α= 5%).The result showed that there were not significantly between temperature and pH to TT, TF and TAAB.The treatmen with lower of total tannin 0.579 mg/100 g and higher of total phenolic 0.224 mg GAE/g is combination between temperature of 30oC and pH of 5.5 for 48 hours. The present work showed that tannin hydrolysis efficiency of Albertisia papuana using this method was 41.7%.